2010
DOI: 10.1117/12.860366
|View full text |Cite
|
Sign up to set email alerts
|

Solution processed OTFTs for OLED backplanes: development of high performance short channel length devices

Abstract: High performance short channel OTFTs with field effect mobilities greater than 1cm 2 V -1 s -1 have been developed for OLED driver applications incorporating soluble crystalline semiconductor materials. We highlight the impact of contact resistance on the mobility in these devices and show by functionalising both the source and drain contacts and channel regions in a top gate bottom contact device architecture that the mobility can be significantly improved. Our approach also includes the optimisation of solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[1][2][3][4] However, care has to be taken with respect to thin film processing conditions because measured mobility values can vary significantly across a single substrate. 5 Recent reports have shown that when an oligoacene is blended with a suitable polymer an improvement in both OTFT performance and reproducibility can be observed. [6][7][8][9][10][11][12][13][14][15][16][17] 6,13-Bis(triisopropylsilylethnyl) pentacene (TIPS-pentacene) when blended with an insulating polymer has been shown by several groups to give good OTFT performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, care has to be taken with respect to thin film processing conditions because measured mobility values can vary significantly across a single substrate. 5 Recent reports have shown that when an oligoacene is blended with a suitable polymer an improvement in both OTFT performance and reproducibility can be observed. [6][7][8][9][10][11][12][13][14][15][16][17] 6,13-Bis(triisopropylsilylethnyl) pentacene (TIPS-pentacene) when blended with an insulating polymer has been shown by several groups to give good OTFT performance.…”
Section: Introductionmentioning
confidence: 99%